1995
DOI: 10.1084/jem.181.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Transient perturbation of endothelial integrity induced by natural antibodies and complement.

Abstract: SummaryThe barrier function of blood vessels is thought to be regulated at least in part by endothelium. This concept is supported by the dramatic loss of barrier function occurring in the hyperacute rejection of vascularized grafts mediated by anti-endothelial ceU (EC) antibodies and complement. In this process, the endothelium is not destroyed but instead loses the ability to retain blood cells and plasma proteins within capillaries. The noncytotoxic mechanism that allows this change in EC function has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(101 citation statements)
references
References 52 publications
2
98
0
1
Order By: Relevance
“…Many substances are able to adversely modify the EC junction, including thrombin (23), antibodies and EC antigen-binding lectins (11,13), and the membrane attack complex of complement (24). Because the injury caused by complement can be prevented by IL-4 (5), we hypothesized that IL-4 modifies one or more components of the junction so that the EC monolayer can resist the deleterious effect of complement.…”
Section: Discussionmentioning
confidence: 99%
“…Many substances are able to adversely modify the EC junction, including thrombin (23), antibodies and EC antigen-binding lectins (11,13), and the membrane attack complex of complement (24). Because the injury caused by complement can be prevented by IL-4 (5), we hypothesized that IL-4 modifies one or more components of the junction so that the EC monolayer can resist the deleterious effect of complement.…”
Section: Discussionmentioning
confidence: 99%
“…Nondestructive endothelial cell separations may involve cytoskeletal alterations, 29 as well as increased endothelial permeability. It is well established that cytokines capable of affecting endothelial cells, e.g., interleukins and tumor necrosis factor ␣ may be released by infiltrating macrophages, 30 activated Kupffer cells, 23 or even endothelial cells themselves.…”
Section: Discussionmentioning
confidence: 99%
“…101,102 AECAs, have been reported to be found in approximately 40% of SLE patients compared to multiple sclerosis, stroke and healthy controls in one study by Saadi and Platt. 103 The IgG from the SLE patients caused increased IL-6 release from IL-1ÎČ pre-treated endothelial cells, compared to control IgG. Another study demonstrated the ability of a monoclonal AECA isolated from an SLE patient to recognize a 42kDa endothelial cell membrane protein and activate endothelial cells, leading to up regulation of the generegulatory protein NF-ÎșB, which is also implicated in a pro-inflammatory milieu.…”
Section: Autoantibodiesmentioning
confidence: 99%